#TITLE_ALTERNATIVE# - EKO WATI (NIM : 10105032); Pembimbing Tugas Akhir : Prof. Dr. Sutawanir Darwis, SUNDARI
One of the characteristic of a reservoir rock is that it must be permeable. Permeable means, the pores of the rock must be connected together so that oil can move from one pore to another. The method that used to estimate the permeability in this final project is called Ensemble Kalman Filter (EnKF). In doing history matching, Ensemble Kalman Filter provides an approximate solution to the combined parameter and state estimation problem. The result is an ensemble of solutions approximating the posterior pdf for model parameters (porosity, permeability), state variables (pressure, saturation), and production data, conditioned to production history. By using the application of Ensemble Kalman Filter in History Matching, we can predict the rate of the oil and the reservoir characteristic, which has a condition constant pressure production and no flow.